ANALISIS AKAD-AKAD PADA BANK PERTANIAN DI SUDAN DAN POTENSI APLIKASINYA PADA LEMBAGA KEUANGAN SYARIAH DI INDONESIA - ZAID, ZAID; IBDALSYAH, IBDALSYAH; AYUNIYYAH, QURROH (Kasaba, 2022)
Indonesia, known for its agriculture, has not fully utilized its natural resources and human capital, leading to a decline in agricultural land and poor welfare for farmers. This has resulted in a lack of interest in farming among the younger generation. Islam offers solutions through contracts like muzaro'ah, musaqah, and salam, which can improve farmers' welfare in Indonesia. A qualitative research study focused on the Agricultural Bank of Sudan, a government-owned bank with over 60 years of experience in agricultural financing. The bank adheres to Sharia principles and offers facilities like storage warehouses and financing options such as murabahah, bai taqsith, mudhorobah, salam, muqowalah, and qardhul hasan to support farmers and the microfinance sector. The bank also requires guarantees from customers and conducts feasibility studies to manage risks associated with agricultural financing. To advance Indonesia's agricultural sector, it is suggested to establish a specialized agricultural financial institution or adopt existing contracts used by agricultural banks globally in Islamic financial institutions. This can help improve farmers' prosperity and make farming a more attractive and sustainable occupation. By implementing these strategies, Indonesia can enhance its agricultural sector and uplift the welfare of farmers who play a crucial role in the country's economy.